The functions of University of Leiden's Malay language reading materials among Malaysian children - Nik Muhamad Affendi, Nik Rafidah; Awang Pawi, Awang Azman; Abd Rahim, Normaliza (Canadian Center of Science and Education, 2019)
The discovery of special collection of Malay language children’s stories at University of Leiden, Netherlands proves that the traditional Malay community cares for appropriate reading material for children. Based on Teuku Iskandar's note in the Catalogue of Malay, Minangkabau, and South Sumatran Manuscripts in The Netherlands, there are many stories of children in the archipelago that are stored in University of Leiden’s Library, Netherlands. However, in this study the researchers only examine three stories in the Children's Story 26 May 1862 Collection. The stories in the collection do not have specific titles, only known as Story 1, Story 2 and Story 3 and 2 stories are contained in the collection of Parable stories. This disclosure is made because there is an opinion that the folklore today is hardly recognizable by the younger generation. This universal issue encourages the researchers to look into old Malay manuscripts and their relevance in the context of children today. Hence the objectives of this study are to classify and analyze folklore functions towards children. Hence, the method of the study involves 450 children randomly chosen according to the zones, the north, south, east and west zones of Peninsular Malaysia, as well as the Sabah and Sarawak zones. The findings show that there are still folk tales that have certain functions that can benefit children. The findings also show that children today are less vulnerable to the stories of their ancestral heritage.